The Influence of Work Ethic, Work Discipline, And Motivation on The Work Productivity of PT Pelindo (Persero) Employees - Siburian, Wenny Indriyaty; Samrin, Samrin (Utan Kayu Publishing, 2025)
This study aims to determine and analyze, partially and simultaneously, the positive and significant influence of work ethic, work discipline, and motivation on employee productivity at PT Pelindo (Persero). The method used in this study was a quantitative approach. The sample size was 81 respondents. The data obtained were primary data through a questionnaire. The analysis used multiple linear regression analysis using SPSS Version 24. The results of this study indicate that work ethic has a partial positive and significant effect on work productivity, work discipline has a partial positive and significant effect on work productivity, and motivation has a partial positive and significant effect on work productivity. Work ethic, work discipline, and motivation simultaneously have a significant effect on employee productivity at PT Pelindo (Persero).